Metal Node Control of Brønsted Acidity in Heterobimetallic Titanium-Organic Frameworks - Rubio-Gaspar, Ana; Navalón, Sergio; Tatay, Sergio; Cirujano, Francisco G; Fernández-Conde, Carmen; Padial, Natalia M; Martí-Gastaldo, Carlos (Journal of the American Chemical Society, 2023)
Compared to indirect framework modification, synthetic control of cluster composition can be used to gain direct access to catalytic activities exclusive of specific metal combinations. We demonstrate this concept by testing the aminolysis of epoxides with a family of isostructural mesoporous frameworks featuring five combinations of homometallic and heterobimetallic metal-oxo trimers (Fe , Ti , TiFe , TiCo , and TiNi ). Only TiFe nodes display activities comparable to benchmark catalysts based on grafting of strong acids, which here originate from the combination of Lewis Ti and Brønsted Fe -OH acid sites. The applicability of MUV-101(Fe) to the synthesis of β-amino alcohols is demonstrated with a scope that also includes the gram scale synthesis of propranolol, a natural β-blocker listed as an essential medicine by the World Health Organization, with excellent yield and selectivity.